2013
DOI: 10.1039/c2sm26945g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of regeneration of liquid silk fibroin on its structure and characterization

Abstract: Silk derived from cocoons of the female silkworm (Bombyx mori) was made into three kinds of test material, degummed fiber, liquid fibroin and regenerated silk fibroin membrane (RSFM). The effect of the silk degumming and fiber dissolution system (SD-FDS) on the molecular structure and properties of silk fibroin were studied in detail. Degumming with Na 2 CO 3 solution had the greatest impact on silk fibroin fiber, resulting in significant reduction of the thermal stability and crystallinity, and the fiber tens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
112
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(118 citation statements)
references
References 27 publications
6
112
0
Order By: Relevance
“…Similar with degumming, studies have reported that differences in the molecular weight of regenerated SF also correlates with the extent of protein degradation induced by various factors of the dissolving process, thus contributing to changes in performance of SF-based materials (Yamada et al, 2001;Wang et al, 2011Wang and Zhang, 2013;You et al, 2013). Wang and coworkers studied the effects of fiber dissolution on the molecular chain of SF when using different inorganic solvent systems including LiBr, and CaCl 2 -EtOH .…”
Section: Fiber Dissolution Considerationsmentioning
confidence: 95%
See 2 more Smart Citations
“…Similar with degumming, studies have reported that differences in the molecular weight of regenerated SF also correlates with the extent of protein degradation induced by various factors of the dissolving process, thus contributing to changes in performance of SF-based materials (Yamada et al, 2001;Wang et al, 2011Wang and Zhang, 2013;You et al, 2013). Wang and coworkers studied the effects of fiber dissolution on the molecular chain of SF when using different inorganic solvent systems including LiBr, and CaCl 2 -EtOH .…”
Section: Fiber Dissolution Considerationsmentioning
confidence: 95%
“…A study by Wang et al reported that the thermal and mechanical properties of SF protein were least affected when using 8.0 M urea as the degumming reagent. SF prepared with this degumming procedure showed the least amount of fracturing in the silk peptide chain, yielding the most intact silk protein similar to natural SF found in vivo in the silk glands of the silkworm (Wang and Zhang, 2013).…”
Section: Silk Biomaterials Fabricationmentioning
confidence: 97%
See 1 more Smart Citation
“…The dried fibroin was dissolved with 9.3 M lithium bromide solution at 70°C for 4 h. The viscous sol obtained after dissolution was dialyzed against deionized water for 48 h to remove the salts. 0.5 mL of the obtained regenerated silk fibroin (RSF) solution was placed in a weighing boat and allowed to dry overnight under hood at room temperature to estimate the concentration of the solution, and, if needed, adjusted to be 6% (w/v) by diluting with deionized water [33].…”
Section: Preparation Of the Regenerated Silk Fibroin (Rsf) Solutionmentioning
confidence: 99%
“…Sericin coats SF chains and the sericin must be removed in a ''degumming'' step-although SF chains can be degraded during this step as a result of the strength of the degumming reagent and degumming time and temperature [23][24][25][26]. The resultant SF molecular weight has a significant effect on the gelation kinetics since the formation of a polymer gel is related to the degree of polymer chain overlap in solution.…”
Section: Introductionmentioning
confidence: 99%